Characteristics of Morphological and Anatomical Mango (Mangifera indica L.) in Nambo and Laroue, East Bungku, Morowali - Karim, Hartono; Samudin, Sakka; Maemunah, Maemunah (Tadulako University, 2018)
This study aims to determine the characteristics of mango plants relied on morphological and anatomical leaf of mango plants in the villages of Nambo and Laroue,subdistrict of East Bungku, Morowali district. An observation of morphological features was conducted in Nambo and Laroue, whereas anatomical observations had been made in the laboratory of Biotechnology, Faculty of Mathematics and Natural Sciences, University Tadulako, from April to July in 2016. The morphological parameters observed includedage of the plant, plant height, stem diameter, canopy diameter, canopy shape and color bars. The alteration of leaf anatomy consists of the size of the stomata, the size of the epidermis, and stomatal index. Moreover, the resulthighlightsmorphological and anatomical characters observed on cluster analysis, described in the form of a dendrogram.The implication of the cluster analysis for two villages resultsin four accessions, namely NM1, NM2, NM15 and LR4 that can be benefited as the planting material of quality mango seeds which will be cultivated.